Why women chose unassisted home birth in Malaysia: a qualitative study - Nur Amani Natasha Ahmad Tajuddin; Julia Suhaimi; Siti Nurkamilla Ramdzan; Khasnur Abd Malek; Ilham Ameera Ismail; Nurainul Hana Shamsuddin; Ahmad Ihsan Abu Bakar; Sajaratulnisah Othman (BMC, 2020)
Abstract Background Incidences of unassisted home birthing practices have been increasing in Malaysia despite the accessibility to safe and affordable child birthing facilities. We aimed to explore the reasons for women to make such decisions. Methods Twelve women participated in in-depth interviews. They were recruited using a snowballing approach. The interviews were supported by a topic guide which was developed based on the Theory of Planned Behaviour and previous literature. The interviews were audio-recorded, transcribed verbatim and analysed using thematic analysis. Results Women in this study described a range of birthing experiences and personal beliefs as to why they chose unassisted home birth. Four themes emerged from the interviews; i) preferred birthing experience, ii) birth is a natural process, iii) expressing autonomy and iv) faith. Such decision to birth at home unassisted was firm and steadfast despite the possible risks and complications that can occur. Giving birth is perceived to occur naturally regardless of assistance, and unassisted home birth provides the preferred environment which health facilities in Malaysia may lack. They believed that they were in control of the birth processes apart from fulfilling the spiritual beliefs. Conclusions Women may choose unassisted home birth to express their personal views and values, at the expense of the health risks. Apart from increasing mothers' awareness of the possible complications arising from unassisted home births, urgent efforts are needed to provide better birth experiences in healthcare facilities that resonate with the mothers' beliefs and values.